2005
DOI: 10.1111/j.1601-6343.2005.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Short hard palate in prenatal trisomy 21

Abstract: The main conclusion of our study is that the total palatal length in prenatal trisomy 21 is shorter than normal and that this is due both to a shortness of the maxillary and the palatine components of the hard palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…One ML distance, representing the width of the maxilla (ld 8-to-9), demonstrates significantly reduced growth in width of the trisomic palate. The reduced growth of the palate contributes to an overall short snout in adult Ts65Dn mice and parallels the reduced growth of the maxilla and palate noted in DS individuals (Fischer-Brandies, 1988;Skrinjaric et al 2004;Lauridsen et al 2005).…”
Section: Palatementioning
confidence: 76%
“…One ML distance, representing the width of the maxilla (ld 8-to-9), demonstrates significantly reduced growth in width of the trisomic palate. The reduced growth of the palate contributes to an overall short snout in adult Ts65Dn mice and parallels the reduced growth of the maxilla and palate noted in DS individuals (Fischer-Brandies, 1988;Skrinjaric et al 2004;Lauridsen et al 2005).…”
Section: Palatementioning
confidence: 76%
“…The findings of this study suggest that measurement of PFSR in the second trimester of pregnancy may be effective in screening for trisomy 21. This novel measurement exploits a combination of two common differences between trisomy 21 and euploid fetuses: increased skin thickening1–4, 11, 12 and midface hypoplasia13, 14, 16–18. It is reproducible and is independent of gestational age within the range of 15–25 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Allanson et al 18 specifically found that maxillary growth in relation to the mandible is decreased. Lauridsen et al 11 measured the overall palatal length and the maxillary and palatine bones separately in aborted fetuses with trisomy 21 between 16 and 25 weeks' gestation. They compared these to measurements in matched euploid fetuses and found that the total palatal length was shorter in trisomy 21 fetuses, due to shortness of both maxillary and palatine components of the hard palate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shapiro et al examined 153 patients with trisomy 21 at 7–66 years of age and reported that the length of the palate was below the 2.5 th centile of the normal range in 95%8. Lauridsen et al examined 31 aborted fetuses with trisomy 21 at 16–25 weeks of gestation, and reported that both components of the hard palate, the maxilla and the palatine bones were shorter than in chromosomally normal fetuses9.…”
Section: Discussionmentioning
confidence: 99%